Evaluation of Tennis Sports Developmen in Pekanbaru City - Jumadi Jumadi; Damrah Damrah (Universitas PGRI Palembang, 2023)
The problem in this study is to determine the evaluation of tennis sports coaching in Pekanbaru City through management organizations, facilities and infrastructure, athlete development, coaches, funding, training programs, and parental support. This type of research uses the CIPP evaluation model, namely (Context, Input, Process, Product). Data collection techniques used are observation, interviews, and documents. Data analysis techniques through: (1) data reduction (2) data presentation (3) data collection (4) conclusions and data verification (5) final conclusions. The results of research through context are still quite good because the athletes, coaches are not accompanied in such a way by the administrators. In terms of input through management organizations, facilities and infrastructure, coaching athletes, coaches, funding, training programs, and parental support is still quite good. Apart from that, the process which includes funding, training programs and parental support is still quite good because there is still a lot that needs to be fixed. In terms of product, the achievements achieved are still relatively low, because the athletes who perform at this club can only compete at the Riau level, for the National level it still needs to be improved in sustainable development. In conclusion, the evaluation of tennis sports development in Pekanbaru City based on context, input, process and product perspectives is in a fairly good category.